Optimization of Vitamin C and Antioxidant Activity in Jelly Candies through the Addition of Tomato Juice and Red Guava - Fitriyah Zulfa; Alfi Nur Rochmah; Yenny Febriana Ramadhan Abdi; Dininurilmi Putri Suleman; Dini Nadhilah; Prajwalita Rukmakharisma Rizki; Dea Yoana Putri (Universitas Ahmad Dahlan, 2026)
Adding functional foods to confectionery can increase children's nutritional intake. Gummy candy is a type of confectionery that children enjoy. It contains high sugar but low nutritional value. The innovation of adding fruit extracts rich in vitamin C and antioxidants from abundant local foods, such as tomatoes and red guava, was expected to improve the gummy candy's chemical properties. This research contributes to improving the chemical characteristics and sensory acceptability of gummy candy by adding tomato and red guava extract. The ingredients are tomato and red guava juice, gelatin, high-fructose syrup, sucrose, and citric acid. Treatments Formula F0, F1, F2, and F3 received 0, 10, 30, and 30% tomato juice and 0, 10, 20, and 30% red guava. The results of sensory testing showed that the panelists preferred the F3 gummy candy formulation. Chemical characteristics show that the addition of red guava extract increases the moisture content, vitamin C, antioxidants, and total soluble solids. In F0, the moisture content was 31.14%, vitamin C 0.21 mg, antioxidant activity 21.63%, and total soluble solids 30.17 mg/L. The optimal treatment at F3 produced a moisture content of 40.19%, total soluble solids of 35.83 oBrix, antioxidant activity of 34.56%, and vitamin C of 1.61 mg. Adding tomato and red guava juice to gummy sweets can increase their vitamin C and antioxidant content. Gummy candy is a nutritious food that tastes good and has enough vitamin C and antioxidants for people to consume.